Algebra and coding theory : virtual conference in honor of Tariq Rizvi, Noncommutative rings and their Applications VII, July 5-7, 2021, Université d'Artois, Lens, France : virtual conference on Quadratic forms, rings and codes, July 8, 2021, Université d'Artois, Lens, France - Noncommutative Rings and Their Applications (Conference); Virtual Conference on Quadratic Forms, Rings and Codes; Leroy, Andre (Andre Gerard); Jain, S. K. (Surender Kumar) (Contemporary Mathematics, 2023)
This volume contains the proceedings of the Virtual Conference on Noncommutative Rings and their Applications VII, in honor of Tariq Rizvi, held from July 5-7, 2021, and the Virtual Conference on Quadratic Forms, Rings and Codes, held on July 8, 2021, both of which were hosted by the Universite d'Artois, Lens, France.The articles cover topics in commutative and noncommutative algebra and applications to coding theory. In some papers, applications of Frobenius rings, the skew group rings, and iterated Ore extensions to coding theory are discussed. Other papers discuss classical topics, such as Utumi rings, Baer rings, nil and nilpotent algebras, and Brauer groups. Still other articles are devoted to various aspects of the elementwise study for rings and modules. Lastly, this volume includes papers dealing with questions in homological algebra and lattice theory. The articles in this volume show the vivacity of the research of noncommutative rings and its influence on other subjects.